2018
DOI: 10.18632/oncotarget.24178
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4 as a prognostic factor for survival in various cancers: a meta-analysis

Abstract: BackgroundAccumulating evidence showed that high expression of toll like receptor 4 (TLR4) was significantly associated with the outcome of patients with solid cancers. However, other studies failed to draw a similar conclusion. Thus, a systematic meta-analysis was performed to assess the prognostic value of TLR4 in solid tumors.ResultsData from 15 studies and 1294 patients were enrolled. Among the 15 studies, 14 studies demonstrated the association between overall survival(OS) and TLR4 expression, and 7 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…TLR4, the receptor for lipopolysaccharide (LPS), primarily induces inflammatory cytokines in immune cells,28 but it is also involved in carcinogenesis and cancer cell survival. Although TLR4 expression has been reported in a variety of tumors,8,9,11,29 TLR4 expression in patients with PTCL had not been studied. In the present study, we found that high expression of TLR4 was observed in 41.7% of all PTCL patients (60/144), and most frequently in patients with PTCL-NOS (58.8%) and ALK + ALCL (50.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4, the receptor for lipopolysaccharide (LPS), primarily induces inflammatory cytokines in immune cells,28 but it is also involved in carcinogenesis and cancer cell survival. Although TLR4 expression has been reported in a variety of tumors,8,9,11,29 TLR4 expression in patients with PTCL had not been studied. In the present study, we found that high expression of TLR4 was observed in 41.7% of all PTCL patients (60/144), and most frequently in patients with PTCL-NOS (58.8%) and ALK + ALCL (50.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, TLR4 expression was thought to be restricted to immune cells, but recent studies have shown that TLR4 is also highly expressed in some types of cancer cells, including colon cancer,6,7 pancreatic ductal adenocarcinoma,8 non-small cell lung cancer,9 and hepatocyte carcinoma 10. Some researchers have shown that high TLR4 expression is related to poor prognosis in malignant diseases,6,9,11 while others have failed to come to a similar conclusion 8. For PTCL, the significance of TLR4 expression has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the majority of clinical studies showed that TLR4 expression strongly correlates with poor prognosis due to increased tumor size [72], stage [73], loss of differentiation [74], chemoresistance [73,75], venous invasion [72], lymph node metastasis [72,[75][76][77][78], recurrence [79], and shorter patient survival [77,80] (Table 1). A recently published meta-analysis examining data from 15 independent encompassing analyses of different tumors from 1294 patients found strong associations (P-values 0.001-0.05) between TLR4 expression and reduced overall and disease-free survival [81]. Collectively, these studies demonstrate high expression of TLR4 in a variety of human solid tumors suggesting it plays a prominent role in inflammation-fueled cancer progression and metastasis.…”
Section: Tlr4 Expression In Malignant Tumorsmentioning
confidence: 88%
“…On the other hand, we observed that pioglitazone reversed the proliferative effect of LPS on B16F10 cells in all concentrations. The effect of TLR4 on cancer progression has been shown in prostate, 28 breast, 29 ovarian 30 and lung cancer 31 and it is upregulated in different cancer cells. Activation of TLR4 can inhibit melanoma cell death while TLR4 inhibition led to inhibition of their survival.…”
Section: Discussionmentioning
confidence: 99%